Light Sum Accumulation in ZnSe Crystals at X-Ray Excitation - V. Ya. Degoda; G. P. Podust; M. Alizadeh (Advances in Condensed Matter Physics)
This paper presents the results of the dose dependencies of the light sum accumulation in ZnSe single crystals at a different X-ray excitation at 85 K. The values of light sum accumulation at different deep traps were determined from the thermally stimulated luminescence and conductivity curves. It was confirmed that the accumulated light sum is uniquely determined by the dose of radiation only, that is, the product of the intensity of excitation by the time of X-ray exposure. The same result is also given by the theoretical consideration of the kinetics of the light sum accumulation on deep traps for a multicenter model of crystal phosphors.